Effects of heavy metals on the expression of a zinc-inducible metallothionein-III gene and antioxidant enzyme activities in Crassostrea gigas - Cong, Ming (Ecotoxicology (London, England), 2012)
Sequestration by metallothioneins and antioxidant defense are two kinds of important defense mechanisms employed by mollusks to minimize adverse effects caused by heavy metal contaminants in marine environment. In the present study, a novel metallothionein gene, CgMT-III, was cloned from Crassostrea gigas, consisting of eighteen conserved cysteine residues and encoding a MT III-like protein with two tandem β domains. The expression level of CgMT-III transcript induced by zinc was much higher than that induced by cadmium exposure. It suggested that CgMT-III was perhaps mainly involved in homeostatic control of zinc metabolism, which was distinct from previously identified MTs in C. gigas. Among the tested antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), SOD and GPx showed varying up-regulations in a tissue-specific manner, while CAT activities were inhibited in both gill and hepatopancreas from C. gigas exposed to heavy metals. It can be inferred that CgMT-III was mainly involved in zinc homeostasis, and CgMT-III gene together with CAT enzyme could be potential biomarkers to indicate heavy metal, especially zinc pollution in marine organisms